(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Access to safe drinking water is a means of poverty alleviation and socio-economic development of a nation. Interventions to improve the quality of drinking water will provide significant benefits to health. The activity concentration of \(^60\)Co, \(^134\)Cs, \(^137\)Cs, and \(^241\)Am measured in twenty (20) ground water sources from three industrial zones of Ogun State using gamma spectroscopy techniques. The mean activity concentrations were found to be \(^60\)Co (0.15\(±\)0.03Bq/l); \(^134\)Cs (0.15(\(±\)0.04Bq/l); \(^ 137\)Cs (0.17\(±\) 0.05Bq/l) and \(^241\)Am (0.69\(±\)0.20Bq/l). Three samples (AB1, JB2 and ID1) recorded high activity of \(^241\)Am above the guidance level of 1 Bq/l recommended by the World Health Organization (WHO). The estimated mean total annual effective dose for three age groups, infant; children and adult are: 0.08 mSv y\(^-1\); 0.06 mSvy\(^-1\); and 0.11 mSv y\(^-1\) respectively. The recommended WHO standard of 0.1 mSv y\(^-1\) was exceeded for adult.This implies that other than nuclear accidents manmade radionuclides can be found in drinking water at a rate higher than the recommended permissible limit. Also, the tendency for higher dose to be recorded in the nearest future will be inevitable if the source of contamination is not controlled. Therefore, anthropogenic activities influencing the concentrations of radioisotopes in the study environment should be checkmate and remediation action implemented. This will promote tangible health benefits to the populace.